Implementation of RESTful Web Service as Employee Data Integration on Oracle Database Technology and MariaDB - Prih Diantono Abda`u; Nur Wahyu Rahadi; Andesita Prihantara (Politeknik Piksi Ganesha Indonesia, 2021)
Computer computer-based information systems at an institution are often built in stages and separately. Data integration between subsystems is not well connected. The results in differences in the data structures or the number of records between one subsystem and another so that the data presented is not aligned. This study aims to design and implement a RESTful Web Service so that other information subsystems can use employee data from the Management Information System. The four stages in this research are observing the information system currently running, analyzing the data integration needs, designing and coding the RESTful Web Service API, implementing and testing the response time.